2019
DOI: 10.1071/rs19006
|View full text |Cite
|
Sign up to set email alerts
|

A heatwave forecast service for Australia

Abstract: The Australian Bureau of Meteorology monitors, researches, predicts and communicates Australia's weather and climate. Australia's mean temperature has risen by over 1°C since 1910, leading to an increase in the frequency of extreme heat events. Extreme heat can profoundly impact human health, infrastructure and the environment. Research conducted at the Bureau and elsewhere shows that climate change is impacting the intensity and frequency of extreme heat events. One way that the Bureau has responded to this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The latest report by the Intergovernmental Panel on Climate Change (IPCC) states that Australia will keep getting hotter, resulting in a need to use mechanical means to achieve comfortable temperature indoors [24]. The record 2012-2013 and 2013-2014 summer temperature reflect this shift to more hot weather events [23], including the January 2014 heatwave in southeast Australia [25]. The January 2019 heatwave is worth mentioning with respect to the duration and the average maximum temperature in Australia and Victoria, respectively [26].…”
Section: Introductionmentioning
confidence: 99%
“…The latest report by the Intergovernmental Panel on Climate Change (IPCC) states that Australia will keep getting hotter, resulting in a need to use mechanical means to achieve comfortable temperature indoors [24]. The record 2012-2013 and 2013-2014 summer temperature reflect this shift to more hot weather events [23], including the January 2014 heatwave in southeast Australia [25]. The January 2019 heatwave is worth mentioning with respect to the duration and the average maximum temperature in Australia and Victoria, respectively [26].…”
Section: Introductionmentioning
confidence: 99%
“…This forecast uses the excess heat factor (EHF) metric – a measure of three‐day heat load that indicates unusually hot conditions for a location relative to both recent and historical average temperatures 28 . The EHF metric allows for harmonised operation of the HHWS in different climatic areas of the state 29,30 …”
Section: Resultsmentioning
confidence: 99%
“…28 The EHF metric allows for harmonised operation of the HHWS in different climatic areas of the state. 29,30 Upon activation for a severe or extreme heatwave by the…”
Section: Activation Of the Hhwsmentioning
confidence: 99%
“…The oceanic climate, with typical cloudy weather, is influenced by the nearby sea and land breezes. Climate change in recent years has led to rising temperatures in temperate maritime climate regions [8]. A study in Sendai, Japan, showed that the sea breeze during the daytime had a cooling effect on the city [9].…”
Section: Introductionmentioning
confidence: 99%